Knowledge, attitude and practice regarding use of fixed dose combination drugs among young prescribers a tertiary care teaching hospital in rural Bengal, India - Mandal, Ananya; Mandal, Sonai; Das, Somenath (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Use of fixed dose combination (FDCs) is a double edged sword with scope for irrational prescribing on one hand and improved pharmacotherapy and patient compliance on the other hand. Irrational FDCs are being marketed aggressively and often young prescribers including Post Graduate Trainees fall prey to the lure of FDCs. This was a Knowledge-Attitude-Practice study regarding of FDC use among the resident doctors working at a tertiary care medical college of rural Bengal. Methods: This was a cross-sectional, questionnaire based study including 50 resident doctors who were asked to fill a 10-question questionnaire on FDCs anonymously. Results: Ninety two percent of the study participants were aware of the FDCs. The most commonly perceived advantages were better patient compliance and synergistic effects. Most (96%) cited problems of titrating dosages and problems of more side effects. Only 37.6% knew about the banned FDCs. Preferred FDCs among them were antibiotics (94%), cough syrups (80%) and NSAIDs (68%). Residents of dermatology, orthopaedics, surgery and medicine most commonly prescribed FDCs. Sources of knowledge regarding FDCs were CME (92%), medical representative (76%), colleagues (72%), internet (68%), journals (48%) and textbooks (36%). Conclusions: The study showed that most participants were aware of the FDCs and also aware of the problems with irrational FDC use. Knowledge regarding banned drugs was poor as was the rationality of such combinations. More CMEs and inter department group discussions could be conducted to improve awareness and FDC prescribing practice among young prescribers.